THE PROBLEMS OF LANGUAGE LEARNERS AND THE IMPORTANCE OF A FOREIGN LANGUAGE IN OUR LIVES - Oygul To‘xtayeva Erkin qizi; Erdanov Zafar Daminovich (Scholars Digest Publishing, 2023)
This article also talks about the problems foreign language learners face and some solutions for them. An opinion is also given on the importance of a foreign language in our life.
Keywords: English grammar, motivation, voice, recommendations, pronunciation, risks, goal, speech activity, knowledge.